Социализация личности в пространстве интернета - Андреева, А. Ю. (ХНУРЕ, 2019)
The article is devoted to the problem of personality socialization in the conditions of dynamically developing virtual reality. Thanks to the Internet a personality socializes in a modem society and masters its behavioral norms and values much more faster and effectively